Impact of continuous pharmaceutical care led by clinical pharmacists during transitions of care on medication adherence and clinical outcomes for patients with coronary heart disease: a prospective cohort study - Gao, Lingyan; Han, Yalei; Jia, Zhankun; Wang, Pengfei; Zhang, Meijing; Ma, Teng; Yan, Suying; Liu, Hua (Frontiers in Pharmacology, 2023)
The study aimed to explore the impact of a continuous pharmaceutical care (CPC) program during care transitions on medication adherence and clinical outcomes for patients with coronary heart disease (CHD). A prospective cohort study was conducted. Patients diagnosed with CHD were selected and divided into intervention (CPC) and usual care (UC) groups by nurses at equal intervals based on admission time. The intervention group received CPC services provided by clinical pharmacists (including medication reconciliation, disease education, medication guidance, lifestyle counseling, and follow-up services) and usual care. The UC group received only routine medical care. The study compared medication adherence, clinical indicators (low-density lipoprotein cholesterol [LDL-C], blood pressure [BP], glycated hemoglobin [HbA1c] control rates), the incidence of adverse drug reactions (ADRs), and readmission rates (overall, major adverse cardiovascular events [MACEs]-related, and CHD risk factors-related) at admission and 1, 3, and 6 months after discharge between the two groups. A total of 228 patients with CHD completed the study (113 in CPC group and 115 in UC group). A total of 101 drug-related problems were identified in the CPC group. The CPC group showed significantly higher medication adherence at 1, 3, and 6 months after discharge than the UC group (P<0.05). At 3 and 6 months after discharge, the intervention group had significantly higher control rates of LDL-C (61.11% vs. 44.64% at 3 months, 78.18% vs. 51.43% at 6 months), and BP (91.15% vs. 77.39% at 3 months, 88.50% vs. 77.19% at 6 months). The CPC group had higher HbA1c control rates (53.85% vs. 34.21% at 3 months, 54.05% vs. 38.46% at 6 months) than the UC group. The incidence of ADRs six months after discharge was significantly lower in the CPC group than in the UC group (5.13% vs. 12.17%, P<0.05). The CPC group had a lower overall readmission rate (13.27% vs. 20.00%), MACE-related readmission rate (5.31% vs. 12.17%), and readmission rate related to CHD risk factors (0.88% vs. 2.61%) six months after discharge compared to the UC group. CPC led by clinical pharmacists during care transitions effectively improved medication adherence, safety, and risk factor control in patients with CHD.